WHO/ILO work-related burden of disease and injury: Protocol for systematic reviews of occupational exposure to solar ultraviolet radiation and of the effect of occupational exposure to solar ultraviolet radiation on cataract. (April 2019) - Tenkate, Thomas; Adam, Balazs; Al-Rifai, Rami H.; Chou, B. Ralph; Gobba, Fabriziomaria; Ivanov, Ivan D.; Leppink, Nancy; Loney, Tom; Pega, Frank; Peters, Cheryl E.; Prüss-Üstün, Annette M.; Silva Paulo, Marilia; et al.
Abstract: Background: The World Health Organization (WHO) and the International Labour Organization (ILO) are developing a joint methodology for estimating the national and global work-related burden of disease and injury (WHO/ILO joint methodology), with contributions from a large network of experts. Here, we present the protocol for two systematic reviews of parameters for estimating the number of disability-adjusted life years of cataracts from occupational exposure to solar ultraviolet radiation, to inform the development of the WHO/ILO joint methodology. Objectives: We aim to systematically review studies on occupational exposure to solar ultraviolet radiation (Systematic Review 1) and systematically review and meta-analyse estimates of the effect of occupational exposure to solar ultraviolet radiation on the development of cataract (Systematic Review 2), applying the Navigation Guide systematic review methodology as an organizing framework and conducting both systematic reviews in tandem and in a harmonized way. Data sources: Separately for Systematic Reviews 1 and 2, we will search electronic academic databases for potentially relevant records from published and unpublished studies, including Ovid Medline, PubMed, EMBASE, and Web of Sciences. We will also search electronic grey literature databases, Internet search engines and organizational websites; hand search reference list of previous systematic reviews and included study records; and consult additional experts. Study eligibility and criteria: We will include working-age (≥15 years) workers in WHO and/or ILO Member States, but exclude children (<15 years) and unpaid domestic workers. For Systematic Review 1, we will include quantitative studies on the prevalence of relevant levels of occupational exposure to solar ultraviolet radiation and of the total working time spent outdoors from 1960 to 2018, stratified by sex, age, country and industrial sector or occupation. For Systematic Review 2, we will include randomized controlled trials, cohort studies, case-control studies and other non-randomized intervention studies with an estimate of the effect of any occupational exposure to solar ultraviolet radiation (i.e. ≥30 Jm −2 /day of occupational solar UV exposure at the surface of the eye) on the prevalence or incidence of cataract, compared with the theoretical minimum risk exposure level (i.e. <30 Jm −2 /day of occupational solar UV exposure at the surface of the eye). Study appraisal and synthesis methods: At least two review authors will independently screen titles and abstracts against the eligibility criteria at a first stage and full texts of potentially eligible records at a second stage, followed by extraction of data from qualifying studies. At least two review authors will assess risk of bias and the quality of evidence, using the most suited tools currently available. For Systematic Review 2, if feasible, we will combine relative risks using meta-analysis. We will report results using the guidelines for accurate and transparent health estimates reporting (GATHER) for Systematic Review 1 and the preferred reporting items for systematic reviews and meta-analyses guidelines (PRISMA) for Systematic Review 2. PROSPERO registration: CRD42018098897. Highlights: WHO and ILO are developing a joint methodology for estimating the national and global work-related burden of disease and injury. This article presents a protocol for two systematic reviews for the development of this WHO/ILO joint methodology. Prevalence studies on occupational exposure to solar ultraviolet radiation will be systematically reviewed. Studies on effects of occupational exposure to solar ultraviolet radiation on cataract will be systematically reviewed and meta-analysed.